(untitled) - Michael E. Brumbach; Michael E. Brumbach (Clifton Park, NY, 2005)
Thoroughly modernized content and a more logical flow of information are just two of the many enhancements heralded in this completely revamped Seventh Edition. Over 850 updated illustrations and photos clarify the fundamentals of electrical theory for use by electrical students and maintenance technicians alike. Coverage begins with electrical symbols and drawings, current, voltage, resistance, and power. Subsequent chapters examine Ohm's law; series, parallel, and combination circuits; and resistive and reactive circuits. Advanced material, including rotating machinery, motor controls, transformers, electronic drives, and PLCs, is also thoroughly discussed
Keywords: Electrical engineering